The Politics of Intermediality in African Theatre Contexts - Makhumula, Catherine (Intermédialités / Intermediality)

(untitled) (Revue intermédialités (Presses de l’Université de Montréal), 2017)
In this article, I discuss the politics of intermediality in African theatre contexts. My underlying assumption is that the study of intermediality is inevitably contextual in nature because intermediality is strongly linked to the sociopolitical and economic context. Jens Schröter explores the links between intermediality and ideological/politico-economic factors in his article “The Politics of Intermediality.” He argues that questions concerning intermediality are by no means purely theoretical or aesthetic questions; rather, they are laden with political connotations. Following Schröter, my approach emphasizes how different cultures understand media differences and their interaction in a given historical phase. Using examples from the Southern region of the African continent, this article navigates through divergent theories of African theatre in its attempt to understand how media interrelations are conceptualized within the theoretical discourses in the region.